Health systems, mechanisms of governance, and governmental porosity in a comparative perspective - Ribeiro, Jose Mendes (2023)
This paper presents a comparative analysis of ten selected countries regarding the established relationships of participative  governance, socioeconomic profiles, and  health care systems with health outcomes  and Global Governance Indicators.  Significant sources were databases  produced or compiled by the World Bank.  The analytical model adopts an  institutionalist approach to address social  protection and participative governance –  the latter, as used, recovers notions of  societal participation, government porosity,  and responsive regulation. Outcomes show  a solid convergence of more distributive  socioeconomic profiles, more universalist  health systems with higher government  financing, and better governance indicators. This analysis supports the  arguments that  socially virtuous institutional paths  subjected to positive feedback favor better  social and political outcomes over time. Analysis is supported in data about health  sector policies and World Governance  Indicators. The results sustain arguments of more socially protective relations with  quality of democratic institutions and  participative governance, government  porosity, greater public financing in health  sector, delivery, and better health results.  Institutional configurations stablished along time reveals convergence in terms of  greater protection or greater vulnerability  according to capacity and quality of public  institutions considering government  porosity, societal participation, and  government capacity in health policies.